Pengaruh Kompensasi Manajemen Dan Corporate Governance Terhadap Manajemen Pajak - Dina Fransiska; Dirvi Surya Abbas; Indra Gunawan Siregar (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The purpose of this study is to determine the effect of Management Compensation, and Corporate Governance on Manufacturing companies, the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange (IDX). The population of this study includes Manufacturing companies, the Consumer Goods Industry Sector which are listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The sampling technique used purposive sampling technique. Based on the criteria that have been applied, 11 companies are obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results show that Management Compensation has no effect on Tax Management, the Board of Commissioners has no effect on Tax Management, Independent Commissioner has no effect on Tax Management and the Audit Committee has no effect on Tax Management. Management Compensation and Corporate Governance together have an effect on Tax Management.